GAPURA SEBAGAI DESAIN KOMUNIKASI VISUAL TENUN TROSO KABUPATEN JEPARA - Kukuh Dwi Wijanarko; Nanang Rizali; Ahmad Adib (DeKaVe, 2017)
Gapura as the entrance to tourist sites Troso weaving is very important, because it is a symbol of visual communication design at the forefront of the village entrance. In general, the purpose of this study to find answers that fit with the main problem is how the gate can visualize the concept of brand visual communication to give impact to the development of Troso Jepara Weaving. The research method is descriptive, that is to make an accurate, systematic and factual explanation about the facts and nature of the population or specific location in this sense in research. The Troso weaving gate was originally established in 2012 and was inaugurated by the district governance of Jepara. Prospects after the gate of Troso Weaving can be seen on the Propinsi road from Semarang to downtown Jepara, it is expected that many people come to Troso village, so that entrepreneurs can market directly to buyers without third party intermediaries.